Pengembangan LKPD Berbasis Web pada Materi Kingdom Animalia untuk Meningkatkan Hasil Belajar Siswa - Arafah, Muhammad; Rompegading, Andi Badli; Rahma R, Nur (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to develop Web-based LKPD on animalia material, to find out the improvement of students' biology learning outcomes through the use of valid, practical, and effective Web-based LKPD. This study uses a development research approach (Research and Development). The object of this research is a web-based LKPD on the material kingdom animalia. The validation and trial stages were carried out on the feasibility of Web-based LKPD. Validation by material experts was carried out to obtain advice regarding the feasibility of web-based worksheets in terms of material. The limited trial was carried out using the response questionnaire method from students in class X MIPA 3 SMA Negeri 1 Wajo. The data analysis technique uses a quantitative descriptive analysis technique with a score of five (Likert scale) against a predetermined rating scale category. The results of the study were obtained, the results of the effectiveness test of limited and wide-scale learning outcomes from the results of the T test with a value of Î± <0.01 so that they were declared to have a significant effect. The N-Gain test result is 0.75 in the